2023
DOI: 10.1002/ejp.2080
|View full text |Cite
|
Sign up to set email alerts
|

The selfBACK artificial intelligence‐based smartphone app can improve low back pain outcome even in patients with high levels of depression or stress

Abstract: Background: selfBACK provides individually tailored self-management support for low back pain (LBP) via an artificial intelligence-based smartphone app. We explore whether those with depressive/stress symptoms can benefit from this technology. Methods: Secondary analysis of the selfBACK randomized controlled trial (n = 461). Participants with LBP were randomized to usual care (n = 229), or usual care plus selfBACK (n = 232). Primary outcome: LBP-related disability (Roland-Morris Disability Questionnaire, RMDQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The reports revealed that most of (65.5-98%) the participants who used the AI-based interventions had at least year 12 education. Although some studies reported that more than half of the subjects had a fulltime job, [55][56][57]75 the accounts by Piette et al 50 and Chiauzzi et al 52 reported that just about one third of their participants were fully employed. targeted the management of one or all the biopsychosocial components of chronic low back pain (specific or non-specific).…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports revealed that most of (65.5-98%) the participants who used the AI-based interventions had at least year 12 education. Although some studies reported that more than half of the subjects had a fulltime job, [55][56][57]75 the accounts by Piette et al 50 and Chiauzzi et al 52 reported that just about one third of their participants were fully employed. targeted the management of one or all the biopsychosocial components of chronic low back pain (specific or non-specific).…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Randomized controlled trials made up 34.4% (n= 11) of the research, [49][50][51][52][53][54][55][56][57][58][59] while others were pilot studies, observational studies, quasi-experimental studies, among others (Figure 7).…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Patients using the SelfBACK App were shown to have reduced pain and disability. In a recent study of 461 people with low back pain (Rughani et al, 2023), the SelfBack App was able to improve outcomes for those with high levels of pain and distress. For the purposes of this service evaluation, the combined approach was called SelfSTarT.…”
Section: Startback and Selfback (Evidence-based Innovations)mentioning
confidence: 99%
“…Digital health technologies for CLBP provide diverse treatment and self-management modalities [35,55,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108]. Examples of mobile apps for CLBP include "BackRx" delivering yoga and Pilates exercises for patients with discogenic CLPB [97,109], as well as PainNavigator delivering CLBP management, including education, physical exercises, yoga, and mindfulness [110].…”
Section: Emergence Of Digital Therapeutics For Clbpmentioning
confidence: 99%